2011
DOI: 10.4327/jsnfs.64.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Boysenberry Juice Intake on Lipid Accumulation in Rats

Abstract: Recently, it has often been reported that certain polyphenols are useful for prevention of obesity. However, few investigations have been conducted on the anti-obesity effects of boysenberry polyphenols, including anthocyanins and ellagic acid. Therefore, we examined whether boysenberry juice BJ would prevent obesity in Wistar rats fed normal and high-fat diets containing 5 BJ for 12 weeks. At the end of the feeding period, our data revealed significant decreases in body weight gain, body fat accumulation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Thus, consumption of food containing various polyphenols has attracted much attention to prevent obesity caused by a high-fat diet. We have previously reported BBJ significantly lowered plasma TG levels together with active FAS and cholesterol levels in the liver, leading to the suppression of elevations of total body weight and body fat in an obesity rat model induced by a high-fat diet including 30% lard (13). These findings indicate that BBJ contains beneficial components associated with anti-obesity effects.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, consumption of food containing various polyphenols has attracted much attention to prevent obesity caused by a high-fat diet. We have previously reported BBJ significantly lowered plasma TG levels together with active FAS and cholesterol levels in the liver, leading to the suppression of elevations of total body weight and body fat in an obesity rat model induced by a high-fat diet including 30% lard (13). These findings indicate that BBJ contains beneficial components associated with anti-obesity effects.…”
Section: Discussionmentioning
confidence: 54%
“…We previously reported that long-term feeding of BBJ showed anti-obesity effects in rats served a high-fat diet (13) and significant suppression of postprandial plasma triglyceride (TG) levels were observed together with the lowering of hepatic fatty acid synthase (FAS) activity. Inhibition of TG absorption from gastrointestinal tract is thought to be an effective strategy to prevent obesity.…”
mentioning
confidence: 99%
“…There have been reports that the serum triglyceride levels of guinea pigs fed the HF diet with grape polyphenol for 12 weeks were significantly lowered 31 , and that the increase of serum triglyceride concentrations in rats fed the HF diet with boysenberries lowered because components of boysenberries control or slow fat absorption in the intestine 32 . An antiobesity effect of chlorogenic acid, which is also present in the Haskap phytochemical, has also been reported 33,34 .…”
Section: Figmentioning
confidence: 99%
“…In accord with these results, Tosca et al showed improved serum triglyceride levels in guinea pigs administered grape polyphenol 19 . Similarly, Noguchi et al showed decreased serum triglyceride concentrations in rats fed boysenberries reflecting inhibition of intestinal fat absorption by boysenberry components 25 . Hence, to assess whether aronia polyphenol phytochemicals such as anthocyanin exert similar effects, we investigated the effect of aronia phytochemicals on pancreatic lipase activity Table 6 .…”
Section: Antihyperlipidemic Effects Of Aronia Phytochemicals Inmentioning
confidence: 99%